Spherical-like porous carbon, preparation method and preparation device thereof, and silicon-carbon negative electrode material

Preparation of spherical porous carbon with suspension method has solved the problems of poor spherical porous carbon ratio and block porous carbon structure in the prior art, improved the circulation and rate performance of silicon carbon negative electrode materials, and reduced production costs and process complexity sex.

CN119240693AInactive Publication Date: 2025-01-03SHENZHEN SOLID ADVANCED MATERIALS TECH CO LTD

Patent Information

Application Number
CN202411770831.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the ratio effect of perfect ball porous carbon is poor, while the block porous carbon is easily affected by its structure, and the production process is complex and costly.

Method used

The spherical porous carbon is prepared by the suspension method. The suspension is formed by crushing the porous carbon precursor and thickener and surfactant to form the suspension. The spherical resin is initially cured. After washing, it is extruded and solidified in a hot roll press, and then carbonized and activated. and passivate to form spherical porous carbon, which is used to prepare silicon carbon anode material.

Benefits of technology

The advantages of taking into account both block and spherical porous carbon are achieved, the cycle performance and rate performance of silicon carbon anode materials are improved, and the production cost and process complexity are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240693A_ABST
    Figure CN119240693A_ABST
Patent Text Reader

Abstract

The invention relates to sphere-like porous carbon, a preparation method and a preparation device thereof, and a silicon-carbon negative electrode material. The preparation method of the sphere-like porous carbon comprises the following specific steps: crushing a porous carbon precursor, and adding a thickening agent and a surfactant to obtain a suspension; stirring and heating the suspension, and primarily curing to form surface-cured spherical resin; washing and filtering the spherical resin with the cured surface; the washed spherical resin is transferred to a hot roller press device, the temperature is gradually increased for extrusion curing, and cured sphere-like resin is obtained; the spheroidic resin is preliminarily scattered, sieved and collected, carbonization and activated pore forming are performed in the nitrogen atmosphere, high-temperature passivation is performed in the nitrogen atmosphere after drying, and the required spheroidic porous carbon is obtained after scattering. The spherical-like porous carbon and silicon carbon negative electrode material provided by the invention integrates the advantages of blocky porous carbon and spherical porous carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a quasi-spherical porous carbon and a preparation method and device thereof, and a silicon-carbon negative electrode material. Background Art

[0002] In recent years, with the rapid development of energy storage and conversion technologies, carbon materials have become important materials in lithium-ion batteries, supercapacitors and other energy devices due to their excellent physical and chemical properties, such as high conductivity, large specific surface area and good chemical stability. Although traditional carbon materials such as graphite have high conductivity, they are difficult to meet the needs of high-performance energy storage devices due to their small specific surface area and single pore structure. Porous carbon materials have great application potential in energy storage devices due to their unique pore structure and large specific surface area.

[0003] Among them, porous silicon-carbon negative electrode materials use porous carbon as a carrier, and deposit silicon sources into the pores of porous carbon under a certain temperature and pressure to form silicon-carbon negative electrode materials. Porous carbon is mainly composed of micropores and mesopores. The deposited silicon is separated by the micropores and mesopores of porous carbon. There are no large particles of silicon, and the expansion stress is small. At the same time, the porous structure of porous carbon provides space for the expansion of silicon. Therefore, porous silicon-carbon negative electrode materials have the advantages of good anti-expansion and long cycle performance, and are unanimously recognized as one of the most promising battery negative electrode materials in the future. Porous carbon is the core material of porous silicon-carbon negative electrode materials. The morphology, composition, and pore structure of porous carbon have a significant impact on the performance of porous silicon-carbon negative electrode materials.

[0004] Prior art 1: Patent publication number CN116495731A discloses a porous carbon microsphere, preparation method and application, and silicon-carbon negative electrode material. It adopts an emulsion method starting from bulk polymerization to produce spherical phenolic resin, and then carbonization, physical activation, silane deposition, and secondary carbon coating. Although a perfect sphere with less adhesion satellite sphere can be obtained, its defect is still a perfect sphere, and the problem of cyclic debonding still exists; and the emulsion method is adopted, the process is long, chemical production is required, and the toxicity of raw materials must be controlled. The production process is complicated and the production investment cost is high, and large-scale chemical industry is required.

[0005] Prior art 2: Patent publication number CN111777066A discloses a preparation process of phenolic resin-based spherical activated carbon, which is similar to the above patents. It starts with low molecular raw materials such as phenol and formaldehyde, and then undergoes emulsion polymerization, and then further solidification, carbonization and steam activation under the protection of inert gas, and finally sieving and grading. The particle size is between 30 and 60 mesh (250-550 μm), and it is used in the field of adsorption. Its defects are: they are all produced by large chemical industry, and they are also perfect spherical porous carbon, and the particle size is large. If forced to crush and grade, the spherical morphology will be completely destroyed, which is not suitable for lithium-ion battery materials.

[0006] Prior art 3: Preparation of phenolic resin-based spherical activated carbon and research on its adsorption performance ([D] Chai Baosen, 2016, University of Chinese Academy of Sciences) discloses: using a hydrothermal method to prepare 3.0~6.0μm phenolic resin microspheres, whose surface is not like a perfect sphere, but has severe adhesion. Although the hydrothermal method is more environmentally friendly, its disadvantages are: the preparation method is difficult to scale up, and the adhesion is severe and difficult to separate.

[0007] At present, most porous carbon is irregular block or spherical porous carbon. However, the perfect spherical porous carbon in the existing technology has point-to-point lithium ion conduction, poor rate effect, and the curved surface causes glue debonding during the cyclic expansion and contraction process, resulting in serious cyclic diving. Due to the sharp corners of block porous carbon, it will be superimposed and broken or pierce the diaphragm during the compaction process, resulting in internal micro short circuit, affecting the voltage and capacity of the battery cell.

[0008] Therefore, the existing technology needs to be improved. Summary of the invention

[0009] In the prior art, perfect spherical porous carbon has poor rate effect, and blocky porous carbon, due to its structure, easily affects the voltage and capacity of the battery cell. Therefore, the present invention provides a quasi-spherical porous carbon and a preparation method and device thereof, and a silicon-carbon negative electrode material for solving the above problems.

[0010] To achieve the above object, in a first aspect, the present invention provides a method for preparing spherical porous carbon, which comprises the following specific steps: S1, crushing a porous carbon precursor, adding a thickener and a surfactant to obtain a suspension; S2, stirring and heating the suspension to initially solidify it to form a surface-solidified spherical resin; S3, washing and filtering the surface-cured spherical resin; S4, transferring the washed spherical resin to a hot roller press device, gradually heating it up for extrusion curing to obtain a cured spherical resin; S5, preliminarily breaking up the quasi-spherical resin, sieving and collecting, carbonizing and activating the pores in a nitrogen atmosphere, drying and passivating the quasi-spherical porous carbon in a nitrogen atmosphere at high temperature, and breaking up the quasi-spherical resin.

[0011] In one implementation, in S1, the porous carbon precursor is a phenolic resin with a D50 of 2 to 20 μm; the thickener is any one of polyvinyl alcohol, carboxymethyl cellulose and sodium cellulose sulfonate; the surfactant is an organosilicon surfactant, and the solid content of the suspension is 8 to 15%.

[0012] In one implementation, in S2, specifically includes: stirring the suspension and gradually heating it to 80-120° C., reacting for 10-60 minutes to make the porous carbon precursor spherical and the surface solidified.

[0013] In one implementation, in S3, the washing and filtration is performed by rinsing with deionized water and then performing suction filtration and washing.

[0014] In one implementation, in S4, extrusion deformation is performed by a hot roller press device, the travel speed of the material on the hot roller press device is controlled or the heating track is extended, the heating time is 10 to 30 minutes, and the heating temperature is 150 to 250° C., to obtain a solidified spherical resin.

[0015] In one implementation, in S4, the spherical resin includes any one of an ellipsoidal resin, a potato-shaped resin, a dice-shaped resin, and a pomegranate seed-shaped resin.

[0016] In one implementation, in S5, the carbonization temperature is 500-800°C, and the high-temperature passivation temperature is 600-1400°C; the activation pore formation specifically includes: fully mixing the spherical resin with a chemical activator, and activating and pore forming at a temperature of 700-1000°C; the chemical activator includes any one of alkali, chloride salt and medium-strong acid.

[0017] In a second aspect, the present invention further provides a quasi-spherical porous carbon, which is prepared by any of the above-mentioned methods for preparing quasi-spherical porous carbon.

[0018] In a third aspect, the present invention further provides a device for preparing spherical porous carbon, which is used to prepare the above-mentioned spherical porous carbon, comprising: A pressure tank, used for stirring a suspension consisting of a porous carbon precursor, a thickener and a surfactant, stirring and heating the suspension, and initially solidifying the suspension to form a spherical resin; A ball valve, arranged at the bottom of the pressure tank, for outputting the spherical resin formed by preliminary curing; A washing device, connected to the pressure tank, for washing the spherical resin solidified on the surface; A centrifugal filter device, connected to the washing device, for filtering the washed spherical resin; A hot roller press device, connected to the centrifugal filter device, comprises a transmission crawler and a heating roller arranged on the transmission crawler, and is used for extruding and curing the surface-cured spherical resin until it is completely cured and formed into quasi-spherical porous carbon; The crushing and collecting box is connected to the hot roller press device and is used for crushing and collecting the scraped spherical porous carbon.

[0019] In a fourth aspect, the present invention further provides a silicon-carbon negative electrode material, which includes the above-mentioned spherical porous carbon.

[0020] Beneficial effects: The preparation method of the spherical porous carbon provided by the present invention adopts a two-step method. The first step is a spherical porous carbon process, in which a spherical porous carbon with a solidified surface and a plastic interior is first produced; the second step is to extrude the surface-solidified spherical resin through a pressure extrusion plane, and further solidify and shape it at a high temperature to become a spherical resin, which is further carbonized, activated, washed, passivated, and deposited to form a porous silicon-carbon negative electrode material, thereby taking into account the advantages of both block and spherical porous silicon carbon, which is beneficial to improving the cycle performance and rate performance of batteries prepared from silicon-carbon negative electrode materials; a spherical porous carbon and silicon-carbon negative electrode material that take into account the advantages of both block porous carbon and spherical porous carbon are provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a flow chart of the steps of the method for preparing spherical porous carbon provided by the present invention; Figure 2 It is a structural block diagram of a device for preparing spherical porous carbon provided by the present invention; Figure 3 is a SEM electron microscope image of the spherical porous carbon provided in Example 1; Figure 4 It is a comparison chart of the rate performance of button cells prepared with the silicon-carbon negative electrode materials provided in Example 3 and Comparative Example 1; Figure 5 It is a cycle comparison curve diagram of the button battery prepared with the silicon-carbon negative electrode material provided in Example 3 and Comparative Example 1; In the figure, the reference numerals are respectively as follows: 10, pressure tank; 20, ball valve; 30, main pipeline for conveying materials; 40, washing device; 50, centrifugal filter device; 60, hot roller press device; 70, transmission crawler; 80, heating roller; 90, crushing collection box; The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0023] See also Figure 1 , Figure 1 The present invention provides a method for preparing spherical porous carbon, which comprises the following specific steps: S1, crushing a porous carbon precursor, adding a thickener and a surfactant to obtain a suspension; S2, stirring and heating the suspension to initially solidify it to form a surface-solidified spherical resin; S3, washing and filtering the surface-cured spherical resin; S4, transferring the washed spherical resin to a hot roller press device, gradually heating it up for extrusion curing to obtain a cured spherical resin; S5, preliminarily breaking up the quasi-spherical resin, sieving and collecting, carbonizing and activating the pores in a nitrogen atmosphere, drying and passivating the quasi-spherical porous carbon in a nitrogen atmosphere at high temperature, and breaking up the quasi-spherical resin.

[0024] Specifically, in S1, the porous carbon precursor is a phenolic resin with a D50 of 2 to 20 μm; the thickener is any one of polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC) and sodium cellulose sulfonate; the surfactant is an organic silicon surfactant, and the solid content of the suspension is 8 to 15%. In the present invention, by adopting a suspension method to prepare, a phenolic resin with a certain molecular weight is directly used, the steps of synthesizing resins from small molecules are reduced, the introduction of large chemical production lines is avoided, and the investment in production equipment is reduced.

[0025] In S2, the method specifically includes: stirring the suspension and gradually heating it to 80-120°C, reacting for 10-60 minutes to make the porous carbon precursor spherical and the surface solidified.

[0026] In S3, the washing and filtration is performed by rinsing with deionized water and then performing suction filtration and washing. Preferably, the suction filtration can be circulated 1 to 3 times to clean the thickener and additives on the surface.

[0027] In S4, the material is extruded and deformed by a hot roller press device, the material travel speed on the hot roller press device is controlled or the heating track is extended, the heating time is 10 to 30 minutes, and the heating temperature is 150 to 250° C., to obtain a solidified spherical resin. The spherical resin finally formed includes any one of an ellipsoidal resin, a potato-shaped resin, a dice-shaped resin, and a pomegranate seed-shaped resin. Preferably, the heating process is a gradient heating process.

[0028] In S5, the carbonization temperature is 500-800°C; the activation pore-forming specifically includes: fully mixing the spherical resin with a chemical activator, and activating the pores at a temperature of 700-1000°C; the chemical activator includes any one of an alkali, a chloride salt, and a medium-strong acid. The alkali is KOH or NaOH, the chloride salt includes any one of NaCl, KCl, ZnCl2, and CuCl2, and the medium-strong acid includes any one of HNO3, H2SO4, and H3PO4. After activation, the material is washed until the pH is between 6 and 8, and the metal content of the material is less than 50ppm. After washing, passivation is performed in an inert gas atmosphere, and the temperature of the high-temperature passivation is 600-1400°C.

[0029] See also Figure 2 , Figure 2 The present invention also provides a device for preparing quasi-spherical porous carbon, which is used to prepare the above-mentioned quasi-spherical porous carbon, and includes a pressure tank 10, a spherical valve 20, a main material conveying pipeline 30, a washing device 40, a centrifugal filter device 50, a hot roller press device 60 and a crushing collection box 90.

[0030] Specifically, the pressure tank 10 is used to stir the suspension composed of the porous carbon precursor, the thickener and the surfactant, and stir and heat the suspension to initially solidify it to form a spherical resin; The ball valve 20 is disposed at the bottom of the pressure tank 10 and is used to output the spherical resin formed by preliminary curing; The main material conveying pipeline 30 is used to connect various devices; The washing device 40 is connected to the pressure tank 10 and is used to wash the surface-cured spherical resin; The centrifugal filter device 50 is connected to the washing device 40 and is used to filter the washed spherical resin; The hot roller press device 60 is connected to the centrifugal filter device 50, and includes a transmission crawler 70 and a heating roller 80 arranged on the transmission crawler, which is used to extrude and solidify the surface-cured spherical resin until it is completely cured and formed into spherical porous carbon; wherein the transmission crawler 70 is a transmission crawler with 800-2000 mesh dense stainless steel mesh and high-strength large-pore stainless steel coils superimposed on both sides of the belt; The crushing and collecting box 90 is connected to the hot roller press device 60 and is used to crush and collect the scraped spherical porous carbon.

[0031] The present invention provides a plurality of embodiments and comparative examples to further illustrate the technical solution of the present invention. It should be noted that the following embodiments are carried out by the preparation device of spherical porous carbon provided by the present invention.

[0032] Example 1 The phenolic resin was crushed into a powder with a D50 of 10 μm, and 2% PVA and 1% silicone surfactant were added to form an aqueous suspension with a solid content of 10%. At a speed of 60 rpm, the temperature was gradually raised to 100 ° C, and the reaction was carried out for 0.5 hours until the surface was slightly solidified. Open the bottom valve and transfer to the washing device. After complete washing, transfer to the centrifugal filter device, and repeat twice until there is no additive residue on the surface of the spherical resin. The washed spherical resin was transferred to a hot roller press device. The first roller of the hot roller press device was 100 ° C, the second roller was 120 ° C, the third roller was 150 ° C, the fourth roller was 200 ° C, and the last roller was cooled at room temperature. The fully solidified spherical resin was scraped off by a scraper, entered the scattering device, and passed through a 100-mesh screen to be collected as a solidified resin.

[0033] The collected solidified resin was heated to 600°C for carbonization for 2 hours under nitrogen protection to obtain a carbonized material with a measured volatile matter of 10%. The obtained carbonized material was mixed and crushed with KOH with an alkali-carbon ratio of 2:1, and after being fully mixed, it was activated for 1.5 hours in a nitrogen atmosphere at 850°C to obtain an activated material. The activated porous carbon was washed with water and acid until the residual amount of various metals was within 50ppm and the material was neutral, and then dried in an oven. Finally, in a nitrogen atmosphere, the temperature was raised to 1000°C for passivation for 1.5 hours, and a spherical porous carbon product was obtained after deoxidation.

[0034] The obtained spherical porous carbon was fed into the deposition equipment, and silane gas was introduced for deposition. The parameters were adjusted until the required silicon-carbon ratio was 45:55, and then acetylene gas was introduced for carbon coating. The parameters were adjusted until the specific surface area of ​​the carbon-coated porous silicon carbon was 5m 2 / g or less, the output material is finished porous silicon carbon and the next step of the electrical test is carried out.

[0035] The prepared porous silicon-carbon negative electrode material was mixed with a conductive agent (Super-P) and a binder LA132 (15wt%) in a mass ratio of 70:20:10 to prepare a slurry, which was coated on a copper foil and dried in a vacuum oven to form a negative electrode sheet. A 1 mol / L LiPF6 electrolyte (the volume ratio of ethylene carbonate and diethyl carbonate in the solvent = 1:1) was used, a polypropylene microporous membrane was used as a separator, and a lithium sheet was used as the negative electrode. A button battery was assembled and the electrochemical performance was tested on a blue battery test system. By comparing the changes in specific capacity and first efficiency under different rolling pressures (unrolled, 1.1MPa, etc.), the compressive strength can be seen; the above battery ratio is compared with spherical porous silicon carbon to test the change in cycle retention rate; compared with spherical porous silicon carbon, constant current charge and discharge are performed at 0.1C, 0.3C, 0.5C, 0.8C, 1C, 2C, and 3C for 5 cycles each, with a voltage range of 0.005V~1.5V. The ratio of the 3C specific capacity to the initial 0.1C specific capacity is summarized in Table 1.

[0036] Example 2 The phenolic resin was crushed into a powder with a D50 of 2 μm, and 4% CMC and 2% silicone surfactant were added to form an aqueous suspension with a solid content of 8%. At a speed of 100 rpm, the temperature was gradually raised to 120°C, and the reaction was performed for 0.1 h until the surface was slightly solidified. The bottom valve was opened and transferred to the washing device. After complete washing, it was transferred to the centrifugal filter device, and repeated 3 times until there was no additive residue on the surface of the spherical resin. The washed spherical resin was transferred to a hot roller press device. The first roller of the hot roller press device was 120°C, the second roller was 140°C, the third roller was 180°C, the fourth roller was 220°C, and the last roller was cooled at room temperature. The fully solidified spherical resin was scraped off by a scraper, entered the scattering device, and passed through a 200-mesh screen to be collected as a solidified resin.

[0037] The collected solidified resin was heated to 800°C for carbonization for 2 hours under nitrogen protection to obtain a carbonized material with a measured volatile content of 6%. The obtained carbonized material was mixed and crushed with NaOH with an alkali-to-carbon ratio of 3:1, and after being fully mixed, it was activated for 1.5 hours in a nitrogen atmosphere at 900°C to obtain an activated material. The activated porous carbon was washed with water and acid until the residual amount of various metals was within 50ppm and the material was neutral, and then dried in an oven. Finally, the temperature was raised to 1100°C in a nitrogen atmosphere for passivation for 1.5 hours, and a spherical porous carbon product was obtained after deoxidation.

[0038] The specific steps of preparation of the finished porous silicon carbon and the electrical connection test are the same as those in Example 1, which will not be described in detail.

[0039] Example 3 The phenolic resin was crushed into a powder with a D50 of 20 μm, and 1% sodium cellulose sulfonate and 1% silicone surfactant were added to form an aqueous suspension with a solid content of 15%. At a speed of 80 rpm, the temperature was gradually raised to 100 ° C, and the reaction was performed for 1 hour until the surface was slightly solidified. The bottom valve was opened and transferred to the washing device. After complete washing, it was transferred to the centrifugal filter device, and repeated twice until there was no additive residue on the surface of the spherical resin. The washed spherical resin was transferred to a hot roller press device. The first roller of the hot roller press device was 120 ° C, the second roller was 140 ° C, the third roller was 180 ° C, the fourth roller was 220 ° C, and the last roller was cooled at room temperature. The fully solidified spherical resin was scraped off by a scraper, entered the scattering device, and passed through an 80-mesh screen to be collected as a solidified resin.

[0040] The collected solidified resin was heated to 700°C for carbonization for 2 hours under nitrogen protection to obtain a carbonized material with a measured volatile content of 8%. The obtained carbonized material was crushed and mixed with HNO3 with an acid-carbon ratio of 4:1. After being fully mixed, it was activated for 1.5 hours in a nitrogen atmosphere at 700°C to obtain an activated material. The activated porous carbon was washed with water, alkali, and acid until the residual amount of various metals was within 50ppm and the material was neutral, and then dried in an oven. Finally, the temperature was raised to 1200°C in a nitrogen atmosphere for passivation for 1.5 hours, and a spherical porous carbon product was obtained after deoxidation.

[0041] The specific steps of preparation of the finished porous silicon carbon and the electrical connection test are the same as those in Example 1, which will not be described in detail.

[0042] Example 4 The phenolic resin was crushed into a powder with a D50 of 8 μm, and 2% PVA and 1% silicone surfactant were added to form an aqueous suspension with a solid content of 12%. At a speed of 90 rpm, the temperature was gradually raised to 100 ° C, and the reaction was carried out for 0.4 hours until the surface was slightly solidified. The bottom valve was opened and transferred to the washing device. After complete washing, it was transferred to the centrifugal filter device, and repeated twice until there was no additive residue on the surface of the spherical resin. The washed spherical resin was transferred to a hot roller press device. The first roller of the hot roller press device was 120 ° C, the second roller was 140 ° C, the third roller was 180 ° C, the fourth roller was 220 ° C, and the last roller was cooled at room temperature. The fully solidified spherical resin was scraped off by a scraper, entered the scattering device, and passed through an 80-mesh screen to be collected as a solidified resin.

[0043] The collected solidified resin was heated to 750°C for carbonization for 2 hours under nitrogen protection to obtain a carbonized material with a measured volatile content of 7%. The obtained carbonized material was crushed and mixed with KOH with a 2:1 alkali-carbon ratio. After being fully mixed, it was activated for 1.5 hours in a nitrogen atmosphere at 850°C to obtain an activated material. The activated porous carbon was washed with water, alkali, and acid until the residual amount of various metals was within 50ppm and the material was neutral, and then dried in an oven. Finally, the temperature was raised to 950°C in a nitrogen atmosphere for passivation for 1.5 hours, and a spherical porous carbon product was obtained after deoxidation.

[0044] The specific steps of preparation of the finished porous silicon carbon and the electrical connection test are the same as those in Example 1, which will not be described in detail.

[0045] Example 5 The phenolic resin was crushed into a powder with a D50 of 6 μm, and 3% CMC and 1% silicone surfactant were added to form an aqueous suspension with a solid content of 10%. At a speed of 80 rpm, the temperature was gradually raised to 80 ° C, and the reaction was carried out for 1.5 hours until the surface was slightly solidified. The bottom valve was opened and transferred to the washing device. After complete washing, it was transferred to the centrifugal filter device, and repeated twice until there was no additive residue on the surface of the spherical resin. The washed spherical resin was transferred to a hot roller press device. The first roller of the hot roller press device was 180 ° C, the second roller was 220 ° C, the third roller was 250 ° C, the fourth roller was 300 ° C, and the last roller was cooled at room temperature. The fully solidified spherical resin was scraped off by a scraper, entered the scattering device, and passed through a 150-mesh screen to be collected as a solidified resin.

[0046] The collected solidified resin was heated to 650°C for carbonization for 2 hours under nitrogen protection to obtain a carbonized material with a measured volatile content of 9%. The obtained carbonized material was mixed and crushed with NaOH with an alkali-to-carbon ratio of 2:1, and after being fully mixed, it was activated for 1.5 hours in a nitrogen atmosphere at 850°C to obtain an activated material. The activated porous carbon was washed with water and acid until the residual amount of various metals was within 50ppm and the material was neutral, and then dried in an oven. Finally, in a nitrogen atmosphere, the temperature was raised to 900°C for passivation for 1.5 hours, and a spherical porous carbon product was obtained after deoxidation.

[0047] The specific steps of preparation of the finished porous silicon carbon and the electrical connection test are the same as those in Example 1, which will not be described in detail.

[0048] Table 1, Statistical table of porous carbon pore structures obtained in various embodiments: Table 2. Performance of porous silicon-carbon button batteries obtained in various embodiments: According to the results in Table 1 and Table 2, combined with Figure 4 and Figure 5 ,in, Figure 4 is a comparison chart of the rate performance of button cells prepared with the silicon-carbon negative electrode materials provided in Example 3 and Comparative Example 1, Figure 5 It is a cycle comparison curve diagram of the button battery prepared with the silicon-carbon negative electrode material provided in Example 3 and Comparative Example 1. It can be seen that since a larger specific surface area and pore volume are generally helpful to improve the lithium storage capacity and electrochemical activity, the performance of Example 3 is relatively poor compared to the spherical porous carbon provided in other embodiments. By comparing Example 3 with Comparative Example 1, among the parameters of the performance of the porous silicon-carbon button battery provided in Example 3, although the difference between the uncompacted specific capacity, the uncompacted first efficiency, the 1.1 compacted specific capacity and the 1.1 compacted first efficiency is not large, its 3C / 0.2C retention rate and the cycle retention rate of 180 cycles are significantly better than those of Comparative Example 1, indicating that it has a higher capacity, better initial efficiency, better rate performance and more stable cycle performance. It is further illustrated that the cycle performance and rate performance of the porous silicon-carbon button battery provided in Examples 1 to 5 are significantly better than the perfect spherical porous silicon-carbon button battery provided in Comparative Example 1, and are close to the block porous silicon-carbon button battery provided in Comparative Example 2.

[0049] In summary, the preparation method of spherical porous carbon provided by the present invention is controlled by temperature and time, so that the perfect ball is only solidified on the surface, and the inside is still in a plastic deformable state. In the subsequent extrusion, rolling, shearing and other methods, the resin ball that is not fully solidified is subjected to a unidirectional force, and the perfect resin ball is deformed in an anisotropic manner under the unidirectional force, thereby becoming a spherical resin, and then undergoing high temperature curing to produce a permanent fixed deformation into a spherical resin, after carbonization, activation, washing, passivation, crushing and classification, it becomes a qualified spherical porous carbon. Since the spherical porous silicon carbon has an arc-shaped appearance as a whole, the concerns of irregular block porous silicon carbon piercing the diaphragm can be avoided, and the stress concentration of the spike-shaped area or the cracking caused by mutual squeezing can be reduced; and the spherical shape has an arc surface and a plane, and the contact area of ​​the plane is large, and the bonding force and the transmission area are significantly improved, which is conducive to improving the cycle performance and rate performance, so that the advantages of the block and the sphere can be taken into account, and a better result is obtained, thereby avoiding the defects of both.

[0050] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing spherical porous carbon, characterized in that: The specific steps include: S1, crushing a porous carbon precursor, adding a thickener and a surfactant to obtain a suspension; S2, stirring and heating the suspension to initially solidify it to form a surface-solidified spherical resin; S3, washing and filtering the surface-cured spherical resin; S4, transferring the washed spherical resin to a hot roller press device, gradually heating it up for extrusion curing to obtain a cured spherical resin; S5, preliminarily breaking up the quasi-spherical resin, sieving and collecting, carbonizing and activating the pores in a nitrogen atmosphere, drying and passivating the quasi-spherical porous carbon in a nitrogen atmosphere at high temperature, and breaking up the quasi-spherical resin.

2. The method for preparing spherical porous carbon according to claim 1, characterized in that: In S1, the porous carbon precursor is a phenolic resin with a D50 of 2-20 μm; the thickener is any one of polyvinyl alcohol, carboxymethyl cellulose and sodium cellulose sulfonate; the surfactant is an organosilicon surfactant, and the solid content of the suspension is 8-15%.

3. The method for preparing spherical porous carbon according to claim 1, characterized in that: In S2, the method specifically includes: stirring the suspension and gradually heating it to 80-120°C, reacting for 10-60 minutes to make the porous carbon precursor spherical and the surface solidified.

4. The method for preparing spherical porous carbon according to claim 1, characterized in that: In S3, the washing and filtration is performed by rinsing with deionized water and then performing suction filtration and washing.

5. The method for preparing spherical porous carbon according to claim 1, characterized in that: In S4, extrusion deformation is performed by a hot roller press device, the travel speed of the material on the hot roller press device is controlled or the heating track is extended, the heating time is 10-30 minutes, the heating temperature is 150-250° C., and a solidified spherical resin is obtained.

6. The method for preparing spherical porous carbon according to claim 5, characterized in that: In S4, the spherical resin includes any one of an ellipsoidal resin, a potato-shaped resin, a dice-shaped resin and a pomegranate seed-shaped resin.

7. The method for preparing spherical porous carbon according to claim 1, characterized in that: In S5, the carbonization temperature is 500-800°C, and the high-temperature passivation temperature is 600-1400°C; the activation pore-forming specifically includes: fully mixing the spherical resin with a chemical activator, and activating and pore-forming at a temperature of 700-1000°C; the chemical activator includes any one of alkali, chloride salt and medium-strong acid.

8. A spherical porous carbon, characterized in that: The spherical porous carbon is prepared by the preparation method of any one of claims 1 to 7.

9. A device for preparing spherical porous carbon, characterized in that: For preparing the spherical porous carbon according to claim 8, comprising: A pressure tank, used for stirring a suspension consisting of a porous carbon precursor, a thickener and a surfactant, stirring and heating the suspension, and initially solidifying the suspension to form a spherical resin; A spherical valve, arranged at the bottom of the pressure tank, for outputting the spherical resin formed by preliminary curing; A washing device, connected to the pressure tank, for washing the spherical resin solidified on the surface; A centrifugal filter device, connected to the washing device, for filtering the washed spherical resin; A hot roller press device, connected to the centrifugal filter device, comprising a transmission crawler and a heating roller disposed on the transmission crawler, for extruding and curing the surface-cured spherical resin until it is completely cured and formed into quasi-spherical porous carbon; and The crushing and collecting box is connected to the hot roller press device and is used for crushing and collecting the scraped spherical porous carbon.

10. A silicon-carbon negative electrode material, characterized in that: The invention comprises the spherical porous carbon as described in claim 8.

Citation Information

Patent Citations

  • Spherical-like porous carbon as well as preparation method and preparation device thereof

    CN119034658A

Cited By

  • Preparation method of lignin-doped sphere-like resin-based porous carbon

    CN121342020A

  • Phenolic resin-based multi-shape silicon-carbon negative electrode material and preparation method thereof

    CN121885604A

  • A phenol-formaldehyde resin-based multi-shape silicon-carbon negative electrode material and a preparation method thereof

    CN121885604B